Corporate Governance Country Assessment : Russian Federation - World Bank (Washington, DC, 2015)
This report assesses Russia's corporate governance policy framework. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Russia. Corporate governance has been a major policy issue in Russia since the beginning of its transition to a market economy. The privatization process of the early 1990s was put in place before most elements of the corporate governance and investor protection framework, and there were many widely publicized abuses, leading to very low asset prices. Most observers agree that the corporate governance environment has improved in recent years as the government has enhanced the legal and policy framework, and key institutions have grown in sophistication and maturity. Many major Russian companies have also voluntarily improved their financial and ownership transparency. A number of reform initiatives are currently underway. The report (and this summary) is organized into four sections: i) the commitment of the public and private sectors to reform; ii) shareholder rights; iii) disclosure and transparency; and iv) Boards of Directors. Policy recommendations are developed in detail at the end of each section. The report also includes a special annex that details the reform agenda focusing on related party transaction approval and disclosure, based on the approach of the Protecting Investors indicator developed in the World Bank's Doing Business report.